PENERAPAN PROBLEM BASED LEARNING BERBANTUAN WEBQUEST UNTUK MENGEMBANGKAN KEMAMPUAN PEMECAHAN MASALAH SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA SEKOLAH DASAR - Kollo, Fredik; Meok, Petrick Yohanis; Henukh, Giovani G.; Radja, Melinda Ratu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to solve problems is an important competence that needs to be developed through Pancasila Education learning in elementary schools. However, learning activities that are less oriented toward problem-solving may limit students' opportunities to analyze problems, seek relevant information, and develop appropriate solutions. This study aimed to determine the effectiveness of Problem Based Learning (PBL) assisted by WebQuest in developing students' problem-solving abilities in Pancasila Education. This study employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The research was conducted at SD Negeri Sikumana 1, Kupang City, involving 60 fifth-grade students consisting of 30 students in the experimental class and 30 students in the control class. Data were collected through pretest and posttest instruments and analyzed using descriptive quantitative analysis and N-Gain. The results showed that the average problem-solving ability of students in the experimental class increased from 60.07 in the pretest to 86.30 in the posttest, with an N-Gain score of 0.659, categorized as moderate. Meanwhile, the control class increased from 61.30 to 68.30, with an N-Gain score of 0.181, categorized as low. These findings indicate that the implementation of PBL assisted by WebQuest resulted in a higher improvement in students' problem-solving abilities than learning in the control class. PBL combined with WebQuest can therefore be used as an alternative learning approach to support active, contextual, and collaborative Pancasila Education learning in elementary schools.